The impact of pig ownership, history of exposure to worms, and personal hygiene on taeniasis infection in Silou Kahean District - Sitanggang, Ismail Juli Rico; Darlan, Dewi Masyithah; Ramayani, Oke Rina; Lubis, Inke Nadia Diniyanti; Hutagalung, Sunna Vyatra (TROPHICO, 2025)
Taeniasis remains a zoonotic public health concern in communities with traditional pig farming systems. Silou Kahean District, Simalungun Regency, is an endemic area where free-range pig husbandry increases exposure risk and may sustain persistent local transmission. This study aims to analyze the relationship between pig ownership status, the number of pigs owned, and pig husbandry practices with the incidence of taeniasis in Silou Kahean District, Simalungun Regency. This cross-sectional quantitative study (October 2024–June 2025, Silou Kahean, Simalungun) analyzed 270 cluster-randomized respondents from a population of 21,149 using structured questionnaires and Kato-Katz fecal examination. Associations between pig ownership, pig density, husbandry method, and taeniasis infection were tested using chi-square (95% CI). The findings revealed a significant relationship between pig ownership and the occurrence of taeniasis (p-value = 0.002; PR = 5.513; 95% CI: 1.953–15.560), indicating that respondents who owned pigs had a higher risk of infection than those who did not. The number of pigs owned also showed a significant association with infection (p-value = 0.035). Furthermore, husbandry methods significantly influenced the occurrence of taeniasis (p-value = 0.0001), with a higher prevalence observed among respondents practicing free-range pig rearing compared to those using pen systems. Pig ownership, higher pig density, and free-range husbandry are significant risk factors for taeniasis in Silou Kahean District. Community education, sanitation improvement, and stronger livestock supervision are critical to interrupt transmission in endemic areas.